2013
DOI: 10.1017/s0272263113000107
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Input and L2 Collocational Processing

Abstract: This study investigated the influence of frequency effects on the processing of congruent (i.e., having an equivalent first language [L1] construction) collocations and incongruent (i.e., not having an equivalent L1 construction) collocations in a second language (L2). An acceptability judgment task was administered to native and advanced nonnative English speakers (L1 Swedish) to assess response times to and error rates for these collocations along with a matched set of unrelated items. The results suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
155
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(178 citation statements)
references
References 48 publications
21
155
2
Order By: Relevance
“…This might suggest that the frequency of the component words that make up collocations may influence learning. Earlier research indicates that the frequency that collocations are encountered affects learning (Webb, Newton, & Chang, 2013), and that the frequency of multiword combinations in English affects the rate with which they are processed by L2 learners (Ellis, Simpson-Vlach, & Maynard, 2008;Sonbul, 2015;Wolter & Gyllstad, 2013). It has also been found that the parts of speech of the component words that make up collocations and the degree of L1-L2 congruency (word for word overlap in L1-L2 form-meaning connection) affects the learnability of multi-word combinations (e.g.…”
Section: The Present Studymentioning
confidence: 99%
“…This might suggest that the frequency of the component words that make up collocations may influence learning. Earlier research indicates that the frequency that collocations are encountered affects learning (Webb, Newton, & Chang, 2013), and that the frequency of multiword combinations in English affects the rate with which they are processed by L2 learners (Ellis, Simpson-Vlach, & Maynard, 2008;Sonbul, 2015;Wolter & Gyllstad, 2013). It has also been found that the parts of speech of the component words that make up collocations and the degree of L1-L2 congruency (word for word overlap in L1-L2 form-meaning connection) affects the learnability of multi-word combinations (e.g.…”
Section: The Present Studymentioning
confidence: 99%
“…The research of Siyanova and Schmitt (2008) showed that "the underlying the intuitions and fluency with collocations of even advanced learners do not seem to match those of native speakers" (p. 429). Moreover, an investigation of reaction time by Yamashita and Jiang (2010) showed that "EFL leaners made more errors with and reacted more slowly to incongruent collocations than congruent collocations" (p. 647), but Wolter and Gyllstad (2013) found that "advanced learners are highly sensitive to frequency effects for L2 collocations" (p. 451).…”
Section: Collocationsmentioning
confidence: 99%
“…Another possible explanation is the participants' prior learning environment. Most of them started learn ing English in a nonEnglishspeaking country and did not have a total im mersion until much later, while such an experience could have positively impacted their collocation skills as discussed in Alsakran's (2011), Groom's (2009), and Wolter and Gyllstad's (2013 research.…”
Section: Discussionmentioning
confidence: 99%
“…keywords: False collocation, second language acquisition (SLA), English as a second lan guage (ESL) Although in the past few decades, the focus of second language acquisition (SLA) research on the lexical proficiency in English as L2 has shifted from individual words as basic lexical units to formulaic word sequences-in par ticular, collocations and factors that influence their acquisition as explored in the studies by Gitsaki (1999), Nesselhauf (2005), Nguyen and Webb (2016), PellicerSánchez (2015), Wolter and Gyllstad (2013), and Ying and O'Neill (2009)-there is still no clear understanding of what factors contribute to or impede collocation acquisition and consequently might predict the condi tions of success in collocation learning and teaching. In part, this is due to the ambiguous nature and the absence of a universally agreed-upon definition or typology of collocations.…”
Section: Une Incertitude Généralisée Plane Quant à La Raison Pour Laqmentioning
confidence: 99%
See 1 more Smart Citation